Plays in time : the beekeeper's daughter, prophecy, another life, extreme whether - Malpede, Karen (Playtext series., 2017)
With commentaries by Marvin Carlson, Christen Clifford, Rebecca Gordon, Cindy Rosenthal, Najla Said and Alexander M. Schlutz.